Relating the neuron doctrine to the cell theory. Should contemporary knowledge change our view of the neuron doctrine? - (:unkn) unknown (ELSEVIER SCIENCE BV, 2007)
The neuron doctrine, formulated in 1891, attacked in 1906 by Golgi and fiercely defended by Cajal, provided a powerful tool for analyzing the pathways of the brain. It has often been described as though it were merely the cell theory applied to nervous systems. In this essay I show that the neuron doctrine claims more than does the cell theory, and that in many instances, where it goes beyond the cell theory, it can no longer be defended on the basis of contemporary evidence. The neuron doctrine should be seen as a practical tool that is particularly useful for understanding the long pathways of the brain; it cannot be regarded as providing an accurate account of what nerve cells in general are really like. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: nerve cell; reticular theory; synapses; golgi; Cajal; STARBURST AMACRINE CELLS; PRESYNAPTIC DEPOLARIZATION; ELECTRICAL SYNAPSES; GANGLION-CELLS; IN-VIVO; INHIBITION; RETINA; NERVE; INTERNEURONS; TRANSPORT